HUBUNGAN ANTARA MUTU PELAYANAN FISIOTERAPI DENGAN KEPUASAN PASIEN PADA INSTALASI RAWAT JALAN POLIKLINIK FISIOTERAPI RSUD KABUPATEN WONOGIRI - Niken Isti Rahayu; Mifbakhuddin - (JURNAL LITBANG, 2004)
Result : Mean of quality by, using survey method with explanatory research as o type of research. From patient mean physiotherapy of RSUD Wonogiri counted more or less 300 patient a determined as service is 21,19 and patient sutisfaction 3,73. The performance service quality stdy in category "enough" counted 57,33% ond " less" counted 42,67%. The level of patient Satisfaction in ctttegory "good" counted 26,66% and "enough" counted 73,34%. The result of statistic analyze a gotten r: 6,55 and p : 0,001 < (0,05). It mean that there a relation between service quality with patient satisfaction.Conclusion : There is a relation between service quality with patient satisfaction at polyclinic physiotherapy of RSUD Wonogiri.Key words: quality of service, satisfaction, physiotherapy service